Analisa Efektifitas Perbaikan Perangkat BTS Telkomsel Karawang dengan iManager u2000 software - Felyta Emasriani; Reni Rahmadewi (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2021)
Recently, the need for cellular telecommunication services in Indonesia being a very large number. The customer growth rate must be supported with the infrastructure development. PT. Telkomsel (one of the provider) has its own way of balancing customer needs with infrastructure development, namely building BTS or Base Transceiver Station. This solution has a negative impact, which affected the PT. Telkomsel loses revenue or loss profit if the BTS experiences damage or interference as a result of continuous use. To reduce this profit loss value, PT. Telkomsel carries out scheduled maintenance or maintenance activities on BTS devices. Based on these problems, the practical work carried out by the author aims to find out and understand the repair or repair procedures on computerized BTS devices at PT. Telkomsel, Karawang. The result of practical work activities is that it is known that the application of a computerized system at PT. Telekomunikasi Selular GraPaRi Karawang helps the process of repairing BTS devices in meeting information needs. To monitor damage to BTS equipment, it is done by means of an alarm monitoring system using the iManager u2000 software.